Overview Development System Experts and Applications In Support Retrieval Decision - Judijanto, Loso (Journal of Exploratory Dynamic Problems, 2024)
Development system expert has in a way significant change the retrieval process decisions in various domains with simulate skill human and giving solution smart . Review article This explore evolution and implementation system expert in taking decision , use approach review combined literature​ with analysis qualitative . Studies This in a way systematic study runway theory system experts , their architecture , and the methodology used in its development . With analyze various literature , research This highlighting role important system expert in increase accuracy decisions , efficiency , and consistency across a wide range of field like maintenance health , finance , and engineering . Findings This underline importance system expert in manage scenario taking complex decisions where expertise​ man Possible limited or No available . Besides the , review This identify trend moment current affairs , challenges , and future directions in development system expert , stressed necessity innovation sustainability and integration with technology new like intelligence creation and learning machine . Study this is very important for academics and practitioners who want to understand potential and limitations system expert in taking decision , give description as comprehensive as possible inform future developments and applications .​ With bridge gap between outlook theoretical and implementation practical , research This contribute to the current discourse taking place about optimization of the picking process decision through solution technology advanced .